2012
DOI: 10.1155/2012/405472
|View full text |Cite
|
Sign up to set email alerts
|

Long Head of the Biceps Pathology Combined with Rotator Cuff Tears

Abstract: The long head of the biceps tendon (LHBT) is an anatomic structure commonly involved in painful shoulder conditions as a result of trauma, degeneration, or overuse. Recent studies have pointed out the close correlation between LHBT lesions and rotator cuff (RCT) tears. Clinicians need to take into account the importance of the LHBT in the presence of other shoulder pathologies. This paper provides an up-to-date overview of recent publications on anatomy, pathophysiology, diagnosis, classification, and current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 62 publications
(74 reference statements)
1
50
0
3
Order By: Relevance
“…This is supported by data from the literature, which indicates that certain tendons tend to fail in hypovascular or critical zones e.g. Achilles tendon, rotator cuff tendons, tibialis posterior tendon [6,7,8]; similarly, in the LHBT a hypovascular area was demonstrated about 1-3 cm from its origin [4].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is supported by data from the literature, which indicates that certain tendons tend to fail in hypovascular or critical zones e.g. Achilles tendon, rotator cuff tendons, tibialis posterior tendon [6,7,8]; similarly, in the LHBT a hypovascular area was demonstrated about 1-3 cm from its origin [4].…”
Section: Introductionsupporting
confidence: 68%
“…Up to 90% of cases of the LHBT tendinopathies are accompanied by additional shoulder disorders, such as massive rotator cuff tears (RCTs); in numerous cases treatment of this condition is difficult [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in shoulder arthroscopy emphasized the importance of LHB tendinopathy in the development of shoulder pain and contributed to a wide use of tenotomy and tenodesis in its management [4]. Microscopic studies of pathological LHBT demonstrated the presence of a degenerative process without pronounced inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Вопросы диагностики и лечения повреж-дений комплекса «суставная губа -длинная головка двуглавой мышцы плеча» приобрета-ют особую актуальность ввиду их частого (40-87%) сочетания с частичными и полнослойны-ми разрывами вращающей манжеты плеча [5,14]. Недооценка этой патологии при выполне-нии реконструкции вращающей манжеты, по данным разных авторов, отрицательно влияет на функциональный исход лечения [1,4].…”
Section: Introductionunclassified